Pengaruh Ukuran Partikel Ampas Kelapa dan Rasio Kacang Tanah pada Karakteristik Snack bar Tinggi Serat - Siti Aisyah; Yuliana Erning Indrastuti; Donor Utomo Muhammad Susilo; Dodi Iskandar; Suharyani Amperawati (PAKIS JOURNAL INSTITUTE, 2026)
Coconut dregs are a byproduct of the coconut oil processing industry, and their utilization as food is limited, even though they still contain crude fiber. This study aimed to analyze the effects of the size and ratio of peanuts and coconut dregs on the physical (color), chemical (water content and crude fiber), and sensory characteristics of snack bars. This study used a Completely Randomized Design (CRD) with two factors: the first factor is size of the coconut dregs (coarse and fine). The second factor was the ratio of coconut dregs to peanuts (15:85, 20:80, and 25:75 g/g). The analysis carried out on the snack bar was water content, fiber content, color (L*, a*, b*, whiteness index and browning index), sensory analysis (taste, color, aroma and texture) and hedonic. The results showed that the size of coconut dregs and the ratio of coconut dregs: peanuts did not affect the water content, b*, aroma, but did affect the fiber content, L*, a*, browning index, sensory taste, color, texture and hedonic. The 25:75 g ratio of coarse coconut dreg to peanuts had the highest preference score, with water and fiber contents of 4.51% and 17.52 %, respectively. The browning index of the snack bar with the highest preference score was the lowest. The coarse coconut dreg had a browning index of 28.80. The browning index of the snack bar with a coconut dreg:peanut ratio of 25:75 g had a browning index of 27.61.